Peculiarities of tissue water fractional composition in case of experimental whole-body hyperthermia - Kuznetsova, O. V. (Regulatory Mechanisms in Biosystems, 2015)
The present study, using proton nuclear magnetic resonance relaxation (NMR) method, was undertaken to compare the water fractional composition in nature tissues (group 1) with those damaged by experimental whole-body hyperthermia (group 2). We measured longitudinal or “spin-lattice” (T1) and transverse or “spin-spin” (T2) relaxation times of protons of tissues (brain, the atria of the heart, the kidneys and the renal cortex) from adult Wistar rats. The differences in T1, T2 and percentage of the intra- and extracellular water between group 1 and 2 were studied to help understand how the water moves in tissues at hyperthermia. The results of this study and the literature data allow to make conclusions about tissue water fractional composition in case of experimental whole-body hyperthermia: (1) fractional composition of water and the distribution of intra- and extracellular fluid in the tissue of the atria of the heart did not change (T1 and T2 relaxation times remained unchanged); (2) the crystalline water fraction increased in brain (longer T1 relaxation rate and shorter T2 relaxation rate). This is obstructing the exchange of protons between free and bound water in brain. Thus, loss of water by brain cells is prevented. The distribution between intra- and extracellular fluid in brain remained unchanged; (3) fraction of free water increased in renal tissue (simultaneous longer T1 and T2 relaxation rates) by reducing the volume of extracellular fluid; (4) thick hydration layer of water (longer T1 relaxation rate, T2 remained unchanged) was formed in the extracellular fluid of renal cortex. This water layer is formed around the sodium ions which concentration is increased in renal cortex tissue of rats from group 2. Аs a result, the amount of fluid secreted by kidneys is reduced, i.e. there is a retention of water in the body. The relevance of our research for the understanding of high temperatures’ adaptation mechanisms is discussed in this paper.